English Investigating the Impact of Social Media Marketing Activities on Buying Decision-Making through the Mediating Role Arabic دراسة تأثير أنشطة التسويق عبر وسائل التواصل الاجتماعي على اتخاذ قرارات الشراء من خلال الدور الوسيط لنتائج استجابة السوق - Dr.aisha Tarek Noour noour (Maǧallaẗ Al-Buḥūṯ Al-Mālīyyaẗ wa Al-Tiğāriyyaẗ)
This research study is to ascertain how the efficiency of social media marketing dimensions influences consumers' buying decision and the role of market response as a mediator. The buying process involves five decision-making steps: recognition, information research, evaluation, purchase decision, and post-purchase. Market response results likewise follow a process, and they can be referred to as determinates because they are based on consumer satisfaction, loyalty, and trust. 385 customers of amazon website from Egypt with a diversity of gender, age, and marital statuses answered the questionnaire in form of data collection. The outcomes demonstrated that buying decision-making and market response outcome had been positively influenced by entertainment, interaction, trendiness, and advertisement. In addition, buying decision-making had been directly correlated with customer trust and customer loyalty. On the flip hand, buying decision-making had been significantly affected by customer satisfaction.Keywords: Social Media Marketing, Customer Trust, Customer Satisfaction, Customer Loyalty and Buying Decision-Making.